Localizing Peptidoglycan Synthesis in Helicobacter pylori using Clickable Metabolic Probes. Issue 4 (12th April 2021) - Taylor, Jennifer A.; Santiago, Cintia C.; Gray, Joe; Wodzanowski, Kimberly A.; DeMeester, Kristen E.; Biboy, Jacob; Vollmer, Waldemar; Grimes, Catherine L.; Salama, Nina R.
Abstract: The bacterial cell wall, composed of peptidoglycan (PG), provides structural integrity for the cell and is responsible for cell shape in most bacteria. Here we present tools to study the cell wall using a clickable PG‐specific sugar, 2‐alkyne muramic acid (MurNAc‐alk), as a metabolic probe. Here we present a new reaction pathway for generating MurNAc‐alk. We also include protocols for labeling PG synthesis in Helicobacter pylori, determining the identity of the labeled muropeptides using LC‐MS/MS, sample preparation of cells labeled for a short fraction of the doubling time, and visualization using 3D structured illumination microscopy. © 2021 Wiley Periodicals LLC. Basic Protocol 1 : Alternative synthesis of MurNAc‐alk (direct coupling) Support Protocol 1 : Growing Helicobacter pylori in liquid culture Support Protocol 2 : Fosfomycin rescue assay Basic Protocol 2 : Mass spectrometry (MS) analysis to determine incorporation of MurNAc‐alk within the peptidoglycan of H. pylori Support Protocol 3 : Hayashi test to determine if SDS is present in the supernatant of peptidoglycan preparations Support Protocol 4 : Creating custom cytocentrifuge units for use in a swinging‐bucket tabletop centrifuge Basic Protocol 3 : Labeling H. pylori with MurNAc‐alk or D ‐Ala‐alk Basic Protocol 4 : Structured illumination microscopy (SIM) imaging on the DeltaVision OMX